Preparation of wastelage with poultry droppings and rice straw (Oryza sativa L.) as a cattle feed - Islam, Obydul; Akter, Somaya; Islam, Md Ahidul; Jamee, Dewan Kamruzzaman; Khan, Rokibul Islam (Asian Journal of Medical and Biological Research, 2018)
The use of poultry droppings as a feed ingredient may not only reduce waste and environmental pollution but also provide inexpensive feed components for ruminants. An experiment was conducted to prepare wastelage in the field laboratory of Animal Science Department, Bangladesh Agricultural University, Mymensingh. Rice straw (Oryza sativa L.) was mixed with 0%, 10%, 20% and 30% caged layer excreta (CLE) and 5% molasses in each treatment on dry matter (DM) basis and ensiled in air tight container under room temperature. After 60 days, ensiled mixture was opened. All the wastelage had desirable smell, light brownish color, soft texture and no fungal growth was found. Results revealed that PH, DM, crude protein (CP), crude fiber (CF), ash, in vitro organic matter digestibility and metabolizable energy were significantly (p<0.05) influenced by different levels of CLE. The highest CP (5.97g/100g DM) was observed in wastelage with 30% CLE (p<0.05) followed by 20% and 10% CLE. The PH level, DM, Ash and CF contents were decreased linearly (p<0.05) from 4.8 to 4.11, 78.00 to 55.63, 25.08 to 17.70 and 22.57 to 14.95%, respectively as the level of CLE increased from 0 to 30%. In all treatments, EE content was not significantly influenced by the different level of CLE. The in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME) also increased significantly (p<0.05) with the increased level of CLE and maximum value (57.51%, and 8.12 MJ/Kg DM, respectively) was obtained in wastelage with 10% CLE, which is statistically identical with 20% CLE. Therefore, it could be speculated that ensiling rice straw with up to 20% CLE improved the feeding value of wastelage. Asian J. Med. Biol. Res. September 2018, 4(3): 251-258